1989
DOI: 10.1139/g89-506
|View full text |Cite
|
Sign up to set email alerts
|

Changes in triticale chromosome heterochromatin visualized by C-banding

Abstract: The distribution and characterization of heterochromatin in a series of cultivars, parents, new amphiploids and progeny of hexaploid triticale were comparatively studied using C-banding and morphometric analysis. A high level of intervarietal polymorphism was detected for the banding pattern. The chromosome pairs 4A and 1R presented the most constant pattern of heterochromatin distribution among 31 triticale lines studied. A total of 126 bands have been catalogued, from which 28, 59, and 39 belong, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Thus, the results collected in this review clearly point out, for the first time, the tendency in cereal-wide hybridization for parental genome size homogenization, which preferentially affects the larger genome to stabilize the newly formed polyploid species. Large scale rearrangement events are also observed resulting from the loss of telomeric heterochromatin, a mechanism used to obtain a more balanced nucleotype in triticale (Jouve et al 1989). Bernardo et al (1988) demonstrated a clear negative effect of rye heterochromatin on triticale meiotic pairing and that the loss of telomeric heterochromatic blocks are related to yield increase in hexaploid triticale (Gustafson and Bennett 1982).…”
Section: Size Matters In Triticale Genome Rearrangements: Larger Genomentioning
confidence: 99%
“…Thus, the results collected in this review clearly point out, for the first time, the tendency in cereal-wide hybridization for parental genome size homogenization, which preferentially affects the larger genome to stabilize the newly formed polyploid species. Large scale rearrangement events are also observed resulting from the loss of telomeric heterochromatin, a mechanism used to obtain a more balanced nucleotype in triticale (Jouve et al 1989). Bernardo et al (1988) demonstrated a clear negative effect of rye heterochromatin on triticale meiotic pairing and that the loss of telomeric heterochromatic blocks are related to yield increase in hexaploid triticale (Gustafson and Bennett 1982).…”
Section: Size Matters In Triticale Genome Rearrangements: Larger Genomentioning
confidence: 99%
“…We anticipate that triticale cultivars may also vary in PMGF. Triticale cultivars are heterogeneous, in part because of their variable genetic background and the amount of retention of the rye genome (Merker, 1971; Jouve et al, 1989; Kuleung et al, 2006). Quantification of PMGF between small plots has implications for the isolation distances used during cultivar development.…”
Section: Resultsmentioning
confidence: 99%
“…Direct tandem fission occurs by two steps: (1) dispersion of centromeres into arms by paracentric inversions and their inactivation, and (2) fissions at the inserted centromeres and their reactivation. Such a repeated dispersion of heterochromatin bands is known to have occurred in a grasshopper species, (Atractomorpha similis) (John & King, 1983), Parascaris equorum (Goday & Pimpinelli, 1986), and some plants such as triticales (Jouve et al, 1989) or Gibasis pulchella (Kenton et al, 1987).…”
Section: Appendix a Tandem Fusions Assumed In The Chromosome Evolutiomentioning
confidence: 99%